Alexithymia Predicts Attrition and Outcome in Weight-Loss Obesity Treatment - Altamura, Mario; Porcelli, Piero; Fairfield, Beth; Malerba, Stefania; Carnevale, Raffaella; Balzotti, Angela; Rossi, Giuseppe; Vendemiale, Gianluigi; Bellomo, Antonello (Frontiers in Psychology, 2018)
Obesity is a psychosomatic condition characterized by a complex interaction of biological and psychological factors. Much research, therefore, has aimed to identify variables limiting efficacy and determining high attrition rates in weight loss programs. In this study, we used the Diagnostic Criteria for Psychosomatic Research (DCPR), designed to broaden the clinician’s perspective on patients’ problems by providing additional clinical information not found in the more traditional psychiatric classification, to predict psychosomatic variables that may limit efficacy and determine attrition in clinical interventions with obese people. We evaluated 82 consecutive participants with obesity at baseline for psychopathology, psychosomatic correlates, psychological distress, and eating-related symptoms before entering a weight loss program. Regression models were used to assess attrition and outcome at a six-month follow-up and per-protocol and intention-to-treat analyses were performed. DPCR alexithymia significantly predicted attrition (OR=6.9), and unsuccessful weight-loss (OR=11.3).These findings suggest that the identification of psychosomatic factors, in addition to psychological and psychopathological factors, may help clinicians to improve adherence to weight-loss programs and likely increase the efficacy of these programs in adults with obesity.